MAKNA DAN NILAI LAGU YANG TERKANDUNG DALAM SYAIR LAGU HAHOLONGI MA SIDOLI KARYA DOMPAK SINAGA SERTA PROSES PENCIPTAANNYA - Nasriani Siregar (Universitas Negeri Medan, 2017)
This study aims to determine the meaning of the valuecontained in the song lyrics haholongi ma Sidoli worksDompak sinaga. The theory used is the meaning, value, Songand Poetry. The meaning is the meaning or intent of a wordthat summed. Values mean something that has a quality angle,song is a composition of the tone or voice. The researchmethod used is descriptive qualitative. This research wasconducted in Humbang Hasundutan and research was startedin December 2015 to February 2016. The study populationwas not there. While the sample is Haholongi Song Ma SidoliDompak Sinaga work as much as one song and DompakSinaga. The results of this study indicate that the meaning ofthe song lyric Haholongi Ma Sidoli were lovers who are notdestined for a brotherly relationship (match). The values onthe song lyric Haholongi Ma Sidoli is: enjoyment value, thevalue of patience, the value of love, psychiatric tilapia, thevalue of life.